Role of primary care enrolment in advanced cervical cancer diagnosis: a population-based case–control study. Issue 1 (27th November 2019) - Bernard, Laurence; Fearon, Danielle; McFaul, Susan; Faught, Wylam
Abstract : Introduction: The elimination of cervical cancer will only be achievable through primary and secondary prevention. The aim of this study was to determine the effect of primary care enrolment on the prevention of advanced cervical cancer. Methods: Using a population-based case–control study, all women (n=5548) above 18 years of age who were diagnosed with cervical cancer between January 2006 and December 2015 in Ontario, Canada were selected for the analysis. The controls were women (n=27 740) above 18 years of age and without a diagnosis of cervical cancer. Five controls were matched to each case by year of birth. Descriptive statistics were used to compare the patients and controls. Multiple imputations and logistic regression were used to estimate the correlation between enrolment with a primary care provider and diagnosis of cervical cancer. Results: A total of 44% of advanced cervical cancer patients and 56% of controls had a screening test 10 years before the index date. The odds of having had a Pap test in the 3 and 10 years before were higher when patients were enrolled with a primary care provider (OR 3.5 and 5.1, p<0.001). The correlation between screening and advanced cervical cancer (stage II–IV) incidence was modified by primary care enrolment: if the patient was enrolled with a primary care provider and had at least one screen in the previous 10 years, the OR of developing advanced cervical cancer was 0.42 (95% CI 0.40 to 0.43); if the patient was not enrolled the OR was 0.78 (95% CI 0.72 to 0.84). Discussion: Primary care enrolment is an effect modifier of cervical cancer screening on advanced cervical cancer incidence. Efforts should be made to increase the capacity of primary care providers to offer screening in order to eradicate cervical cancer.